Atypical presentation and complications of term pregnancy with Mullerian duct anomaly: two case reports - Katoch, Tanvi; Katoch, Manvi (International Journal of Research in Medical Sciences, 2022)
Mullerian duct anomalies present as vague and overlapping features with other gynaecological conditions or may remain asymptomatic. These can lead to various obstetrical complications such as miscarriage, fetal growth restriction, preterm birth, abnormal placental implantation, malpresentation, increased risk of cesarean section, retained placenta and others. We hereby presented two cases with term pregnancy in women with Mullerian duct anomaly and the obstetrical complications they had. The first case landed up in a cesarean section at term due to breech presentation as a result of MDA. The second case had a vaginal delivery followed by entrapped retained placenta due to MDA, which had to be removed in piece meal. We hereby discussed the possible pathophysiology leading to these obstetrical complications in MDA pregnancies. MDA can lead to complications in pregnancy and previously undiagnosed women when detected with MDAs should be informed about complications and treatment options before and during pregnancy, for better maternal and neonatal outcomes.